Robust Control of an Aerial Manipulator Interacting with the Environment⁎. Issue 13 (2018) - Naldi, R.; Macchelli, A.; Mimmo, N.; Marconi, L.
Abstract: This paper deals with the problem of modelling and controlling a vertical take-off and landing aircraft equipped with a lightweight robotic arm. This system is able to perform complex operations that require the physical interaction with the environment while remaining airborne. Once the dynamical model in the 3D case is provided, a control law able to let the degrees of freedom of the system to track a desired trajectory is derived. The proposed controller takes into account the interaction between the robotic arm and the aerial platform both during free-flight and in the presence of unknown contact forces deriving from the interaction with the environment. The effectiveness and main properties of the proposed control algorithm have been analytically investigated and then demonstrated with the help of an experiment.